Calcium and Phosphorus Levels in Saliva are Influenced by Genetic Polymorphisms in Estrogen Receptor Alpha and Microrna17 - Küchler,Erika Calvano (2020)
Abstract Homeostasis between salivary calcium and phosphorus is important for maintaining oral health. The aim of this study was to evaluate if polymorphisms in ESR1 (Estrogen Receptor Alpha), ESR2 (Estrogen Receptor Beta) and miRNA17 (microRNA17) are associated with calcium and phosphorus levels in saliva. Saliva from 276 12-year-old children were collected by masticatory stimulation and calcium and phosphorus levels were determined by Mass Spectrometry. Genomic DNA was extracted from remaining saliva and genetic polymorphisms in ESR1 (rs12154178, rs1884051, rs9340799 and rs2234693), in ESR2 (rs4986938 and rs1256049) and in miRNA17 (rs4284505) were genotyped using TaqMan chemistry and a real-time PCR equipment. Statistical differences in genotype and allele distributions between ‘low’ and ‘high’ calcium and phosphorus levels were determined using chi-square or Fisher´s exact tests. The analysis was also adjusted by sex (alpha of 5%). ESR1 rs9340799 had the less common genotype associated with higher calcium levels (p=0.03). The less common allele of ESR1 rs1884051 was associated with lower phosphorus levels (p=0.005) and there was an excess of heterozygotes for miRNA17 rs4284505 among individuals with lower calcium levels (p=0.002), both adjusted by sex. This study provides evidence that genetic polymorphisms in ESR1 and miRNA17 are involved in determining salivary calcium and phosphorus levels.